Religious Literacy and Restorative Justice with Youth: The Role of Community Service Professionals in Mediating Social Inclusion. Issue 2 (3rd April 2021) - Parker, Christina; Gill, Ravina
Abstract: Community service professionals, such as educators and social workers, are well positioned to support the youth they serve through restorative justice and religious literacy education. Educators and social workers can engage youth in critical conversations that shape young people's experiences in their schools and broader communities. Civic religious literacy can support youth in identifying platforms for engagement and inclusion. In providing opportunities to interrupt bias and marginalization, restorative justice and civic dialogue create a way forward. Young people who are included in school and community groups may be less likely to seek out extremist groups that promote hatred and violence.